Post-radiation MR imaging features in Molecular and Mutational Analyses in Pontine Pediatric Diffuse Midline Gliomas - Rameh, Vanessa; Ziaei, Alireza; Vajapeyam, Sridhar; Chen, Nan; London, Wendy B.; Wright, Karen; Poussaint, Tina Y. (American Journal of Neuroradiology, 2025)
BACKGROUND AND PURPOSE: We aimed to describe the post-radiation imaging features in children with pontine pediatric diffuse midline glioma, and to identify associations between these changes and histone mutational status, as well as overall survival.MATERIALS AND METHODS: Patients were recruited as part of an IRB approved, multicenter clinical trial: Molecularly Determined Treatment of pontine diffuse midline glioma. Subjects had baseline MR imaging that showed classic imaging criteria of pontine diffuse midline glioma and post radiation imaging at regular intervals. All patients underwent biopsy before therapy initiation and received standard radiation therapy with adjuvant bevacizumab. Patients were subsequently stratified based on methylation status and EGFR expression in the biopsy specimen.Imaging analyses included post-radiation T2/FLAIR and enhancing tumor volumes, as well as normalized ADC (nADC) histogram metrics (mean, median, mode, skewness, and kurtosis) at 2 and 4 months post-radiation. The mutation sub-groups were compared using a Wilcoxon rank-sum test.RESULTS: Forty-one patients met eligibility criteria, and mutational status was identified in 35. The median age was 6 years (range: 1.2-17). Seventeen of 35 (49%) had H3-3A histone mutations, 10/35 (29%) had H3C2/3, and 8/35 (22%) were wild type (WT).Except for enhancing volume at RT2, all imaging features had a statistically significant change (p<0.05) from baseline to RT1 and RT2.Within the cohort of patients that had H3-mutant tumors (n=27), patients with H3C2/3 had statistically significantly higher mean nADC_FLAIR (p=0.05), mode nADC_FLAIR (p=0.003), median nADC_FLAIR (p=0.02), and mode nADC-enhancement (p=0.04) than patients with H3-3A at RT1. These nADC histogram metrics were not statistically significantly different at RT2.Moreover, we found no statistically significant difference in ADC histogram metrics post radiation, when we compared H3-mutant versus WT tumors.CONCLUSIONS: Post-radiation MR imaging features are differentially correlated with the underlying mutational status of pediatric pontine diffuse midline glioma.ABBREVIATIONS:Pediatric pontine diffuse midline glioma=pDMG Diffuse intrinsic pontine glioma= DIPG Epidermal growth factor receptor=EGFR Overall survival=OS Radiotherapy=RT Progression-free survival=PFS Contrast-enhanced=CE Post-radiation time point 1 (2 months post-radiation)=RT1 Post-radiation time point 2 (4 months post-radiation)=RT2